SPECIFIC FEATURES OF THE UNITS DENOTING REPROACH IN THE ENGLISH AND UZBEK LANGUAGES - Muxtorova, Moxlaroyim (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This study explores the linguistic and cultural dimensions of reproach expression in English and Uzbek languages. Through semantic, syntactic, and cultural analysis of reproach-denoting units, the study examines the diverse ways in which individuals convey dissatisfaction or disappointment towards others' actions or behaviors. The findings reveal a rich variety of expressions reflecting cultural norms, social values, and interpersonal dynamics. Syntactic analysis uncovers structural patterns shaping the tone and intensity of reproachful expressions, while cultural analysis highlights the importance of considering cultural nuances in interpretation and usage. The study underscores the implications for language learning, translation, and intercultural communication, emphasizing the need for awareness of cultural and linguistic factors in cross-cultural interactions.